Music analysis in Britain in the nineteenth and early twentieth centuries - Dale, Catherine; Zon, Bennett (Aldershot Ashgate, 2003)
Nineteenth-century Britain has often been regarded as a 'land without music' and without 'music analysis' also. This book aims to disprove this notion by reference to the rigorous scientific analytical methods of Williams, Evans and Prout, the pedagogical methods of Hullah, Glover and Curwen and the analytical concert programme notes of Davison, Bennett and Grove. It concludes with a consideration of Tovey, the 'grand old man of British analytical history', and attempts to show the derivation of his methods from these earlier 19th-century practices.